Water sector reforms in Tanzania: is it enough to take us to the MDGs? - Rehema Tukai; Felix Ngamlagosi (2003)
This paper outlines GoT proposed plans and mechanisms for achieving sector targets focusing on investment in RWSS sub-sector. The paper links the proposed plans and mechanisms with issues raised in sector Public Expenditure Reviews (PER) and highlight challenges requiring immediate attention as part of the reform process.